Characterising variation in composition and activation criteria of rapid response and cardiac arrest teams: a survey of Medicare participating hospitals in five American states. Issue 3 (8th March 2019) - Mitchell, Oscar J L; Motschwiller, Caroline W; Horowitz, James M; Evans, Laura E; Mukherjee, Vikramjit
Abstract : Objectives: To characterise the variation in composition, leadership, and activation criteria of rapid response and cardiac arrest teams in five north-eastern states of the USA. Design: Cross-sectional study consisting of a voluntary 46-question survey of acute care hospitals in north-eastern USA. Setting: Acute care hospitals in New York, New Jersey, Rhode Island, Vermont, and Pennsylvania. Participants: Surveys were completed by any member of the rapid response team (RRT) with a working knowledge of team composition and function. Participants were all Medicare-participating acute care hospitals, including teaching and community hospitals as well as hospitals from rural, urban and suburban areas. Results: Out of 378 hospitals, contacts were identified for 303, and 107 surveys were completed. All but two hospitals had an RRT, 70% of which changed members daily. The most common activation criteria were clinical concern (95%), single vital sign abnormalities (77%) and early warning score (59%). Eighty one per cent of hospitals had a dedicated cardiac arrest team. RRT composition varied widely, with respiratory therapists, critical care nurses, physicians and nurse managers being the most likely to attend (89%, 78%, 64% and 51%, respectively). Consistent presence of critical care physicians was uncommon and both cardiac arrest teams and teams were frequently led by trainee physicians, often without senior supervision. Conclusions: As the largest study to date in the USA, we have demonstrated wide heterogeneity, rapid team turnover and a lack of senior supervision of RRT and cardiac arrest teams. These factors likely contribute to the mixed results seen in studies of RRTs.